Wood microbiology : decay and its prevention - Zabel, R. A. (Robert A.) (Academic Press, 2020)
Wood Microbiology, Second Edition, presents the latest advances in wood decay and its prevention. Coverage includes classification of fungi and bacteria, factors affecting growth and survival, fungal metabolism, and wood chemistry. There are also chapters that focus on the anatomical aspects, chemical changes, and ultrastructural effects of wood decay. Additionally, this book discusses major issues associated with wood decay, detecting decay, and how to take protective action against it. This is a one-stop reference resource for wood scientists, wood processing and preserving professionals, foresters and forest pathologists, as well as students of forestry, and wood science and technology courses. It is authored by two leading experts with over 80 years of experience working with timber durability. --